Acquisition of word order in Chinese as a foreign language - Jiang, Wenying, 1965- (Studies on language acquisition ;, 2009)
In this book, linguistic achievements of word order studies in Chinese have been applied to Chinese second language acquisition research. By analyzing a great number of word order errors made by learners of Chinese as a foreign language (CFL), this book has developed a method for describing and explaining Chinese word order errors. With this method, the book has the potential to empower CFL teachers all over the world to teach Chinese in an informed manner, and particularly to teach Chinese word order more effectively and efficiently.